Motivation of Students Majoring Chinese: An Exploratory Study - Li, Leying (2013)
This research reports on a qualitative investigation into what shaped and sustained the motivation of L1-Chinese learners of English. Motivation was not constrained to L2 learning but extended to what the participants considered as the dynamic interplay of personal and contextual factors.